Interference effect of configuration parameters of vertical sand-obstacles on near-surface sand transport - Luo, Xiangying; Li, Jinrong; Tang, Guodong; Li, Yingkun; Wang, Ru; Han, Zhaoen; Feng, Jiaxin; Ren, Tingjie (Frontiers in Environmental Science, 2023)
This study investigates the impacts of height (H) and porosity (P) on the structural properties of wind-driven sand flux in vertical sunflower straw sand-obstacles. We conducted an experiment on sand transport within barriers of various configurations within a 1 m proximity to the surface. In tandem, we monitored wind velocity and direction within the barriers, analyzed total sand transport rate, sandblocking effects, and cumulative sediment transport rate heights for various parameter configurations, and devised a best sand transport flux model for use within the sand-obstacle. The efficacy of vertical sunflower stalk sand-obstacles in mitigating sand movement has been demonstrated to fall within the range of 37.26% to 92.31%. This study reveals a significant correlation between barrier height and porosity in achieving this effect (p<0.05). High and densely configured sand-obstacles lead to an accumulation of intercepted sand material in front of the front row of the sand-obstacle. In contrast, low and sparsely arranged sand-obstacles exhibit a delayed state of sand material accumulation. Furthermore, with an increase in the height of the obstacle and a decrease in porosity, there is a diminishing trend in the sand transport rate within the obstacle. Concurrently, the height of sand transport within the barrier exhibits an upward trend. A three-parameter exponential function has been employed to more precisely simulate the wind-sand flow structure characteristics within a 1-meter height range of the barrier. These research findings contribute to an enhanced understanding of the impact of different vertical sandobstacle configurations on near-surface wind-driven sand transport patterns in active desert areas. Moreover, they furnish both theoretical underpinnings and practical guidance for the scientific configuration of vertical sand-obstacles.